2020
DOI: 10.1111/1365-2656.13288
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fertilizer decreases survival and reproduction of female locusts by increasing plant protein to carbohydrate ratio

Abstract: 1. Nitrogen limitation theory predicts that terrestrial plants should benefit from nitrogen inputs and that herbivores should benefit from subsequent higher plant protein contents. While this pattern has generally been supported, some herbivorous insects have shown preference and higher performance on low protein (p), high carbohydrate (c) diets as juveniles. 2. However, little is known about the effects on reproduction in adults. Using nitrogen fertilizer, we demonstrate that high plant p:c has negative effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 66 publications
3
15
0
Order By: Relevance
“…We also found that G3 locusts preferred millet seeds which are extremely carbohydrate biased and nutrient dense. This result is in accordance with the existing literature on O. senegalensis that describes it as being a pest of seedling millet and soft seeds (Boys 1978) and as preferring carbohydrate biased artificial diets (Le Gall et al 2020a, b) and plants ( Le Gall et al 2020c). While the weed Paspalum scrobiculatum was not readily preferred in the choice experiment to millet, previous work (Toure et al 2013, Word et al 2019, Le Gall et al 2020a) and our current survey data, all showed that at the beginning of the rainy season locusts are more abundant in fallow fields containing mainly weeds of many species than in millet fields.…”
Section: Discussionsupporting
confidence: 92%
“…We also found that G3 locusts preferred millet seeds which are extremely carbohydrate biased and nutrient dense. This result is in accordance with the existing literature on O. senegalensis that describes it as being a pest of seedling millet and soft seeds (Boys 1978) and as preferring carbohydrate biased artificial diets (Le Gall et al 2020a, b) and plants ( Le Gall et al 2020c). While the weed Paspalum scrobiculatum was not readily preferred in the choice experiment to millet, previous work (Toure et al 2013, Word et al 2019, Le Gall et al 2020a) and our current survey data, all showed that at the beginning of the rainy season locusts are more abundant in fallow fields containing mainly weeds of many species than in millet fields.…”
Section: Discussionsupporting
confidence: 92%
“…Further studies on Oedaleus spp. in Senegal and China corroborate the hypothesis that high carbohydrate diets support locust migration [32,33]. Different factors influencing or determining insect outbreaks have been hypothesized including physiological [39] or top-down mechanisms [40].…”
Section: Habitats and Feeding Preferencessupporting
confidence: 68%
“…Also, some studies have measured whole plants, while we measured the leaves, which are the primary food of locusts in the wild. Other recent studies of locust nutritional ecology have also found that the p : c intake targets for locusts tended to be lower than the p : c of available plants [18,21,35].…”
Section: Discussionmentioning
confidence: 86%